2016
DOI: 10.1016/j.jimonfin.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Credit booms, banking crises, and the current account

Abstract: A number of papers have shown that rapid growth in private sector credit is a strong predictor of a banking crisis. This paper will ask if credit growth is itself the cause of a crisis, or is it the combination of credit growth and external deficits? This paper estimates a probabilistic model to find the marginal effect of private sector credit growth on the probability of a banking crisis. The model contains an interaction term between credit growth and the level of the current account, so the marginal effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Previous research has mainly focused on changes of "financial" factors in explaining the occurrence of financial crises in the near future, such as movements in credit (e.g., Mueller, 2017), aggregate stock and house prices (e.g., Anundsen et al, 2016), and external deficits (e.g., Davis et al, 2016). 3,4 Substantial evidence suggests that bank credit expansions play a particular role with respect to financial crises.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has mainly focused on changes of "financial" factors in explaining the occurrence of financial crises in the near future, such as movements in credit (e.g., Mueller, 2017), aggregate stock and house prices (e.g., Anundsen et al, 2016), and external deficits (e.g., Davis et al, 2016). 3,4 Substantial evidence suggests that bank credit expansions play a particular role with respect to financial crises.…”
Section: Introductionmentioning
confidence: 99%
“…Robert Unger (2017) employed panel error-correction specification and showed that flows of bank loans to the non-financial private sector are a significant determinant of the current account and that they -together with changes in competitiveness -constituted the most important factor driving the build-up of current account imbalances in the deficit countries. J. Scott Davis et al (2016) examined the cause of a crisis and found that the combination of credit growth and external deficits increases the probability of a banking crisis. M. Fatih Ekinci, F. Pinar Erdem, and Zubeyir Kilinc (2015) pointed that, at the early stages of financial development, acceleration in credit growth might cause a larger deterioration in the current account balance.…”
Section: Resultsmentioning
confidence: 99%
“…This dataset covers the years 1970-2017. The sample contains 21 advanced and 17 emerging market economies as in Davis et al (2016). The unconditional default frequency is calculated as the total count of default events divided by the total number of country-year pairs.…”
Section: Data Description For Calibrationmentioning
confidence: 99%
“…In the data, we follow the classification inLaeven and Valencia (2013), who use banking sector losses and other indicators to identify banking crises. The list of 38 advanced and emerging economies is as inDavis et al (2016). In the model, we define a banking crisis as a non-zero reduction of bank's capital.…”
mentioning
confidence: 99%